STUDI KONDISI SOSIAL EKONOMI PASANGAN USIA SUBUR KAWIN USIA MUDA DI KANAGARIAN SUNGAI GAMBIR SAKO TAPAN KECAMATAN RANAH AMPEK HULU KABUPATEN PESISIR SELATAN - mutia yudita; Dedi Hermon (JURNAL BUANA, 2021)
The purpose of this study is to find out the Study Of Socioeconomic Condition Of Couples Of Childbearing Age Mating At A Young Age In Nagari sungai Gambir Sako Tapan Sub-District Ranah Ampek Hulu Pesisir selatan District. This study uses a type of descriptive research with a quantitative approach to data collection using observation and polling, as well as for data processing using descriptive statistics. The results of the study are: (1) Economic conditions seen from the fulfillment of food needs have been met, reviewed from the fulfillment of the needs of the sandang has been met, the fulfillment of the needs of the board has not been met properly proven that 55 respondents or (56.70%) have a home that is not in good condition, the median income of 88 respondents or (90.72%) Rp < rp. 1,500,000 per month, at least each family has one working family member, and more than half of respondents or (57.73%) have no savings. (2) Education (PUS) married young people on average after junior high school and elementary school, namely the education of the husband after junior high school (40.20%) and elementary school (39.17%), while the education of the wife finished junior high school (46.39%) and finished elementary school 43 respondents or (44,32%), children aged 7-15 years old are pretty much out of school that is (41.23%), more than half of respondents answered family members who could not read and interpret Latin writing. (3) Health is reviewed if many sick family members still do not take family members to the nearest health facility (45.36%), if PUS wants to use the nearest health service already (28.86%) not go to the nearest health service to use kb, (PUS) who already have 2 or more children already use the kb even though (29,89%) not using kb, on average in the last three months there are still many family members in unwell condition (44.32%). (4) Social conditions are seen from many religions that perform worship even though (37,11%) not performing worship, efforts to improve religious knowledge are still lacking because (55.67%) not trying to improve religious knowledge, interaction and communication in the family is good enough though (36.08%) do not utilize eating together to communicate between family members, social interaction with the community is still lacking, helps make material contributions in less social organizations, and the role in society is lacking